1990
DOI: 10.1210/endo-126-1-88
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin Induction of Interleukin-2 Receptors on Rat Splenic Lymphocytes*

Abstract: A case for the involvement of PRL in the regulation of the immune system is strong. However, no mechanism by which PRL exerts this regulation has yet been identified. We studied the in vitro effects of PRL on splenocytes from ovariectomized (OVX) rats and discovered that PRL induced the formation of interleukin-2 (IL-2) cell surface receptors. However, PRL did not induce IL-2 secretion. This response, which was dependent on the concentration of PRL, also depended upon the estrogen status of the splenocyte dono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(47 citation statements)
references
References 21 publications
1
46
0
Order By: Relevance
“…However, receptors for prolactin (24) and growth hormone (24), which also activate Stat5, are present on lymphoid cells (25)(26)(27). Prolactin increases proliferation of lymphocytes (28,29) and enhances IL-4 production (30).…”
Section: Il-2 Is Important In Th2 Primingmentioning
confidence: 99%
“…However, receptors for prolactin (24) and growth hormone (24), which also activate Stat5, are present on lymphoid cells (25)(26)(27). Prolactin increases proliferation of lymphocytes (28,29) and enhances IL-4 production (30).…”
Section: Il-2 Is Important In Th2 Primingmentioning
confidence: 99%
“…Alternatively, PRL could act indirectly by upregulation of the expression of cytokine receptors, such as IL-2 receptor alpha (IL-2Ra, CD25) as reported for rat splenocytes Revised 24 October 2002; accepted 22 January 2003 (Mukherjee et al, 1990) and for mouse CD4 + and CD8 + T cells (Gala and Shevach, 1993). Prolactin could also upregulate expression of its own receptor on human peripheral blood lymphocytes (Dardenne et al, 1994), including T cells (O'Neal et al, 1991).…”
mentioning
confidence: 99%
“…Russell et al [7] have identified PRL receptors on human PBMCs and have indicated that they were specific for PRL. It has already been reported that PRL could induce IL-2 receptor (CD25) expression in murine lymphocytes [9,10], but the effect of PRL on the expression of CD25 and other activation markers in human lymphocytes has rarely been evaluated. In this paper, we have shown that PRL could significantly enhance the expression of CD69 and CD25 antigen on human PBMCs.…”
Section: Discussionmentioning
confidence: 99%
“…The proliferative response of mouse spleen cells exposed to Con-A was significantly potentiated by PRL [12]. Ornithine decarboxylase (ODC) in human lymphocytes [7] and the formation of IL-2 cell surface receptors on lymphocytes [9,10,13] were induced by PRL. In our experiment, PRL at 1-2 mg/ml significantly enhanced the expression of CD69 and PRL at 0.2-1 mg/ml significantly enhanced the expression of CD25 induced by PHA stimulation, respectively, but PRL alone did not induce the expression of CD69 and CD25.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation